2020
DOI: 10.3390/en13164148
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Aeroacoustic Noise Generation for Vertical Axis Turbines in Close Proximity

Abstract: We present Large Eddy Simulations and aeroacoustic spectra for three configurations of increasing flow complexity: an isolated NACA0012 airfoil, an isolated rotating vertical axis wind turbine composed of three rotating airfoils and a farm of four vertical axis turbines (with identical characteristics as the isolated turbine), which are located in close proximity. The aeroacoustic signatures of the simulated airfoil and the isolated turbine are validated using published numerical and experimental data. We prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…(2) The impact of the varied angle of attack on the tip speed ratio improves the turbine's power efficiency and torque output. However, the downstream and upstream noise intensifies as the angle of attack increases [21]. As a result, noise prediction at take-off must account for the effect of angles of attack.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The impact of the varied angle of attack on the tip speed ratio improves the turbine's power efficiency and torque output. However, the downstream and upstream noise intensifies as the angle of attack increases [21]. As a result, noise prediction at take-off must account for the effect of angles of attack.…”
Section: Discussionmentioning
confidence: 99%
“…The sixth article is entitled "Insights into the aeroacoustic noise generation for vertical axis turbines in close proximity" by Viqueira-Moreira and Ferrer [36]. In this article, the authors predict tonal frequencies, providing theoretical estimates in: an isolated NACA0012 airfoil, an isolated rotating vertical axis wind turbine composed of three rotating airfoils, and a farm of four vertical axis turbines.…”
Section: Summary Of the Contributionsmentioning
confidence: 99%
“…Recently, Kun Wang et al examined the instability characteristics of a twin-turbine (vertical axis) wake with two rotational configurations and reported that the inverse energy cascade process occurs after high-frequency coherent structures [12]. The aeroacoustics signatures of the VAWT are examined using large-eddy simulations and aeroacoustics spectra for different configurations [13]. Particularly, it is stated that the VAWT model is capable of capturing wind from any direction [14,15].…”
Section: Introductionmentioning
confidence: 99%